Literatura in dialog z videoigrami na primeru romanov Puščava, klet, katakombe in Anastrofa - Čeh, Aleš (Jezik in slovstvo, 2020)
The paper explores two novels from the younger generation of Slovenian writers that implement narrative techniques and attributes specific to the video game medium. It places both novels in the broader context of intermediality between video games and literature, and illustrates their transmedial relationship through examples relevant to understanding the magnitude of the phenomenon. Anastrofa, a short novel by Muanis Sinanović, uses video game narrative techniques primarily for space-building within the narrative, whereas the novel-essay Puščava, klet, katakombe by Anja Radaljac enters the dialogue with the video game medium through a more convincing presentation of essayist discourse and a higher degree of reader interaction with the text. Due to the increasing frequency of intermedial transfer between video games and literature in the Slovenian space, the paper provides a pilot analysis of this contemporary narrative phenomenon.
Keywords: litRPG; mediality; medialnost; računalniško igranje vlog; Radaljac, Anja; role-playing video games; Sinanović, Muanis; Slovene literature; Slovene prose; slovenska književnost; slovenska proza; video games; videoigre